Product Renewal in the Field of Family Law in Indonesia - Sugitanata, Arif (Law and Justice, 2021)
This article discusses the product of the family law renewal in Indonesia. Family law is a law that has provisions in the area of munakahat and mawaris. The main focus of the study of this article is why there is family law renewal and what are the products of family law renewal in Indonesia. By using a literature study which materials and data in its arrangement use books and journals related to renewal products in the field of family law in Indonesia, then the data used in this study is a qualitative study, then the method used is descriptive-analytical. found that the appearance of Islamic law renewal, especially in the realm of family law, which developed in this era, in the view of Islamic jurists in Indonesia, is due, first, to fill the legal vacuum caused by the existing rules in classical fiqh books that have not been regulated where the times always demand new rules to answer issues that continue to develop in society. Second, the demands of the modern era of economic development, science and technology which are completely sophisticated. Third, demands for changes in various fields so as to provide space for Islamic law to become a reference in formulating national law. Fourth, demands for renewal of Islamic legal thought from international Islamic jurists to national Islamic jurists, one of which is related to science and technology and issues of gender equality. Then the products of family law renewal in Indonesia are divided into two scopes, namely munakahat and mawaris, where part of munakahat itself includes marriage registration, minimum age restrictions for marriage, the role of marriage guardian, polygamy, interfaith marriage, dowry in marriage, hadhanah and pledge of divorce. Whereas in mawaris includes substitute heirs and wajibah escrow.